1992
DOI: 10.1016/0014-5793(92)80168-g
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of the gene for the merozoite surface antigen MSA2 of the human malaria parasite Plasmodium falciparum during the asexual cycle

Abstract: R~iv~ 27 i~.'¢mbet 1991The transcription of the. Ptam~adhun, ./~dciparmu 8erie, I~r the MSA ~. antigen has been studied throughout the parasite., a~exual 8ro~lh t')~.'~ For this purpose pol,~A) RN,A, IYom dlll~rent tlme~ el the cycle was te~ted for the p~'scnce of the mRNA t,~codmg MSA2 by in vltm trmttlatton attd suhscqlicttt tt,lulysis el the traltslntlon products by Immunoprt'clpitation with un antibody apinst MSA2. TI~ ~ult~ tes~.aled that Ih~mRNA is present in trnpho~oites. ~aches the highest concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
3
1
0
Order By: Relevance
“…This result is consistent with previous reports that MSP2 is not detectable in ring-stage parasites (47,74,75) and is not found in culture supernatant fractions (20,47). Importantly, both the 3D7 and FC27 allelic forms of MSP2 showed the same phenotype of being carried into RBCs followed by rapid degradation.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous reports that MSP2 is not detectable in ring-stage parasites (47,74,75) and is not found in culture supernatant fractions (20,47). Importantly, both the 3D7 and FC27 allelic forms of MSP2 showed the same phenotype of being carried into RBCs followed by rapid degradation.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with previous reports that MSP2 protein is not detectable in ring-stage parasites nor invasion supernatants using a number of different experimental approaches (Ramasamy 1987 ; Clark et al. 1989 ; Barron 1992 ; Pearce et al. 2004 ).…”
Section: Introductionsupporting
confidence: 93%
“…These included two kinases (PFB0665w, a serine threonine kinase and PFB0815w, a calciumdependant proteine kinase), which are thought to be involved in the regulation of the cell cycle, and proteins recognized to play a key role during the infection, such as PFB0300c, the MSP2 antigen, and KAHRP. [12][13][14][15][16] We also observed that seven of the eight SERA antigens were upregulated between the ring stage and the schizont stage. These SERA antigens have been well characterized as putative vaccine candidates and are also thought to play a key role during the infection and are known to be differentially transcribed.…”
Section: Units)supporting
confidence: 55%